The Role of Madrasah Anti Korupsi to Reach Indonesia Clean of Corruption - Franky Ariyady; Gufroni Gufroni (Rechtsidee, 2019)
Crruption virus, has become an epidemic, damages all the joints of our civilization. Based on the data Corruption Perception Index 2016, Indonesia won 37 points last year, improved by one point in 2015 which was recorded 36 points. But still, Indonesia is a corrupt country because it is still below the average of 43 points. Anti-corruption movements must continue to be massively duplicated, all elements of civil society must be part of the anti-corruption movement. The congregation movement against corruption through the Anti-Corruption Madrasa (MAK) is a genetics of the Muhammadiyah movement, since a century ago. From the results of the research, the fact revealed the fight against corruption and building an anti-corruption culture through MAK is a new interpretation of al-maun's theology in the second century of Muhammadiyah today. There are 2 big goals from MAK. First, fostering anti-corruption awareness starts with oneself (ibda bi nafsi). Second, together fighting against corruption by involving other anti-corruption civil society organizations.